Tine options for alleviating compaction in wheelings - Niziolomski, Joanna; Simmons, Robert W.; Rickson, R. Jane; Hann, Michael J. (Elsevier, 2016)
Repeated trafficking and harvesting operations lead to high levels of compaction in inter-row wheelings used in asparagus (Asparagus officinalis) production. This reduces soil porosity and infiltration resulting in water ponding on the soil surface. Even on gently sloping land this can result in runoff generation and an increased risk of soil erosion. A winged tine (WT) is currently used by a leading asparagus grower to loosen compacted inter-row wheelings. In order to test the effectiveness of this tine for alleviating compaction and implications for runoff and soil erosion control, it was evaluated alongside several other tine configurations. These were a narrow tine (NT); a narrow tine with two shallow leading tines (NSLT); a winged tine with two shallow leading tines (WSLT); and a modified para-plough (MPP). Testing was conducted under controlled conditions on a sandy loam soil in the Soil Management Facility at Cranfield University, Bedfordshire, UK. Tine performance was assessed at 3 depths (175, 250 and 300 mm) by draught force; soil disturbance (both above and below ground); specific draught for a given level of soil disturbance; surface roughness; and estimated change in soil bulk density. The effectiveness of tines for compaction alleviation and potential for mitigating runoff and soil erosion varied with depth. The most effective tines were found to be the MPP NSLT and the WSLT at 175 mm, 250 mm and 300 mm depth, respectively.
Keywords: Compaction; Tine; Trafficking